SHRINKAGE AND SWELLING OF SPECIMENS WITH DECREASING DIMENSIONS - Todorova, Martina; Bardarov, Nikolai; Pinchevska, Olena; Sirakova, Emilia (Innovation in Woodworking Industry and Engineering design, 2026)
As the water content changes, the wood cells shrink or swell. These are some of the processes characterizing the variability of wood. They greatly complicate processing and limit the application of wood materials. These properties depend on many factors, one of which is the scale (dimensions) of the wooden samples. Many observations show that the shrinkage and swelling processes proceed differently when the wooden samples is a few millimeters or a few centimeters. There is an even greater difference in the behavior of earlywood and latewood when they are examined separately. The article study the processes of shrinkage and swelling during repeated wetting and drying. Samples with a constantly decreasing cross-section were investigated.